Aktifitas fisik berupa Senam Lansia pada Masa New Normal: Physical activity in the form of Elderly Exercise during the New Normal Period - Siregar, Hasbunsyah; Baiq Emy, Nurmalisa (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2023)
Introduction: The new normal period requires people to implement health protocols including social distancing which requires staying at home. This causes a decrease in community activity, including the elderly, who are a vulnerable group in the transmission of Covid-19. On the other hand, a decrease in the activity of the elderly can lead to reduced immunity and the health of the elderly in general. The aim of this community service is to increase the motivation of elderly people to do elderly exercise by implementing health protocols. Method This community service activity was carried out on June 10 2022. The targets involved in this community service activity were all elderly people and PSTW Tentena Madago administrators. Health promotion in the form of counseling and direct practice of exercise for the elderly is the method used to carry out this community service. Counseling material was carried out before the exercise by emphasizing the importance of physical activity for the elderly during the new normal period as an effort to increase the immunity of the elderly. The results of educational activities and elderly exercise can increase the motivation of elderly people to get involved in elderly exercise at PSTW Madago. Physical activity in the form of exercise for the elderly needs to be routine as an effort to maintain the health of the elderly at PSTW Madago